Click synthesis of 1, 2, 3-triazole based imidazoles: Antitubercular evaluation, molecular docking and HSA binding studies. (15th March 2021) - Pradeep Kumar, C.B.; Prathibha, B.S.; Prasad, K.N.N.; Raghu, M.S.; Prashanth, M.K.; Jayanna, B.K.; Alharthi, Fahad A.; Chandrasekhar, S.; Revanasiddappa, H.D.; Yogesh Kumar, K.
Graphical abstract: Highlights: A series of 1, 2, 3-triazole based imidazole derivatives were synthesized using Click reaction. These compounds showed good anti-tuberculosis activity against Mtb H37Rv. Molecular docking studies figured out the binding interaction of synthesized compounds. ADME properties of synthesized compounds have been predicted. The interaction between HSA and active compounds was studied by spectroscopic techniquies. Abstract: Using Cu(I)-catalyzed cycloaddition of alkyne and azide reaction (CuAAC), a series of novel 1, 2, 3-triazole based imidazole derivatives (3a-e) have been synthesized. The synthesized molecules were characterized by spectroscopic techniques such as 1 H NMR, 13 C NMR, mass and elemental analysis. Antitubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv (Mtb) and cytotoxic activity against the mammalian Vero cell line was screened for the synthesized compounds. The compounds 3d and 3e displayed potent in vitro antitubercular activity and may serve as a lead for further optimization. Besides, the experimental findings were in line with the results of molecular docking. Also, the synthesized compounds have also been analyzed for ADME properties and the experimental finding facilitates the development of new and more potent anti-TB agents in this series in the future. Using fluorescence and UV–vis absorption spectroscopy, the binding interaction of compounds (3d and 3e) with human serum albumin (HSA) was investigated. The results showed that, as a result of HSA-compound complex, the fluorescence quenching of HSA by test compounds was a static quenching process. According to Forster's theory, energy transfer efficiency is calculated.